Into the wedge of N $$ \mathcal{N} $$ = 2 superconformal gauge theories - L. Griguolo; L. Guerrini; A. Testa (Journal of High Energy Physics)
Abstract We study 1 4 $$ \frac{1}{4} $$ -BPS Wilson loops in four-dimensional SU(N) N $$ \mathcal{N} $$ = 2 super-Yang-Mills theories with conformal matter in an arbitrary representation R $$ \mathcal{R} $$ . These operators are formed of two meridians on the two-sphere separated by an arbitrary opening angle. We conjecture that these observables are encoded in a modification of Pestun’s matrix model. The matrix representation of these operators resembles that of the 1 2 $$ \frac{1}{2} $$ -BPS circular Wilson loop, differing only for a rescaling in the exponent. We compare the matrix model predictions with an explicit three-loop calculation in flat space based on standard Feynman-diagram techniques, finding perfect agreement. Finally, exploiting the matrix model representation of these Wilson loops, we study the large-N limit at strong coupling of N $$ \mathcal{N} $$ = 2 superconformal QCD, finding a surprising transition in the vacuum expectation value for a critical opening angle.